Spokane international railway ebook - Jones, Dale W. (Images of Rail., 2019)
The last half of the 19th century was typified by tycoons and shrewd railroad barons. A key figure in the development of the Spokane International Railway was James Jerome Hill, or simply Jim Hill. Spokane businessmen regarded Hill as a tyrant and considered his Great Northern and Northern Pacific railroads unwelcome monopolies in Northeast Washington and the Idaho Panhandle. In 1905, Daniel Chase "D.C." Corbin broke the Hill lines' stronghold by forming the Spokane International Railway as a 140-mile rail line from Spokane, Washington, to Eastport, Idaho, to interchange traffic from the Canadian border to the Pacific. Today, the route continues to be profitable under Union Pacific Railroad ownership with commodities shipped to Western markets via the Canadian Pacific Railway. This book shares the story of the Spokane International Railway and traces its international and local connections with every major railroad in the Pacific Northwest.